Pengaruh Perputaran Kas dan Perputaran Persediaan terhadap Profitabilitas - Iskandar, M Aldo Reynaldo (COMPETITIVE, 2023)
ABSTRACTThis study aims to determine the effect of cash turnover and inventory turnover on profitability. The variables used in this study are cash turnover, inventory turnover and profitability. This research was conducted using quantitative methods with an associative approach.The population in this study is the financial statements of manufacturing companies in the consumer goods industry sub-sector for the 2017-2020 period as many as 11 companies. In this study, sampling was done with saturated sampling technique. Data collection techniques using secondary data. The data analysis technique used is the classical assumption test, multiple linear analysis, and hypothesis testing. The results of this study indicate that partially cash turnover has a negative and significant effect on profitability with the t test results of -3,082 with a significance value of 0.004, while the inventory turnover variable has a positive and significant effect on profitability with the t test results of 4.137 with a significance value of 0.000. Cash turnover and inventory turnover have a simultaneous effect on profitability with f test results of 9.633 with a significance value of 0.000. So it can be concluded that cash turnover and inventory turnover have an effect of only 32.0% on profitability and the rest is influenced by other factors not examined in this study. Keywords: Cash Turnover, Inventory Turnover, Profitability